Half-Brain Delineation for Prediction of Radiation-Induced Temporal Lobe Injury in Nasopharyngeal Carcinoma Receiving Intensity-Modulated Radiotherapy - Du, Qing-Hua; Gan, Yi-Xiu; Wang, Ren-Sheng; Liu, Wen-Qi; Li, Jian; Liang, Fei-Fei; Li, Xiang-De; Zhu, Hui-Jun; Ou, Xue; Zhong, Qiu-Lu; Luo, Dan-Jing; Zhu, Zhi-Peng; et al. (Frontiers in Oncology, 2021)
Purpose: To investigate the role of half-brain delineation in the prediction of radiation-induced temporal lobe injury (TLI) in nasopharyngeal carcinoma (NPC) receiving intensity-modulated radiotherapy (IMRT). Methods and Materials: A total of 220 NPC cases treated with IMRT and concurrent platinum-based chemotherapy were retrospectively analyzed. Dosimetric parameters of temporal lobes, half-brains and brains included maximum dose (Dmax), doses covering certain volume (DV) from 0.03cc to 20cc and absolute volumes receiving specific dose (VD) from 40 Gy to 80 Gy. Inter-structure variability was assessed by coefficients of variation (CV) and paired samples t-tests. Receiver operating characteristic curve (ROC) and Youden index were used for screening dosimetric parameters to predict TLI. Dose/volume response curve was calculated using the logistic dose/volume response model. Results: CVs of brains, left/right half-brains and left/right temporal lobes were 9.72%, 9.96%, 9.77%, 27.85% and 28.34%, respectively. Each DV in temporal lobe was significantly smaller than that in half-brain (P<0.001), and the reduction ranged from 3.10% to 45.98%. The area under the curve (AUC) of DV and VD showed an "increase-maximum-decline" behaviour with a peak as the volume or dose increased. The maximal AUCs of DVs in brain, half-brain and temporal lobe were 0.808 (D2cc), 0.828 (D1.2cc) and 0.806 (D0.6cc), respectively, and the maximal AUCs of VDs were 0.818 (D75Gy), 0.834 (V72Gy) and 0.814 (V70Gy), respectively. The cutoffs of V70Gy (0.86cc), V71Gy (0.72cc), V72Gy (0.60cc) and V73Gy (0.45cc) in half-brain had better Youden index. TD5/5 and TD50/5 of D1.2cc were 58.7 Gy and 80.0 Gy, respectively. The probability of TLI was higher than >13% when V72Gy>0cc, and equal to 50% when V72Gy=7.66cc. Conclusion: Half-brain delineation is a convenient and stable method which could reduce contouring variation and could be used in NPC patients. D1.2cc and V72Gy of half-brain are feasible for TLI prediction model. The dose below 70 Gy may be relatively safe for half-brain. The cutoff points of V70-73Gy could be considered when the high dose is inevitable.